Mass-spring matching layers for high-frequency ultrasound transducers a new technique using vacuum deposition - Brown, Jeremy (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2014)
We have developed a technique of applying multiple matching layers to high-frequency (>30 MHz) imaging transducers, by using carefully controlled vacuum deposition alone. This technique uses a thin mass-spring matching layer approach that was previously described in a low-frequency (1 to 10 MHz) transducer design with epoxied layers. This mass- spring approach is more suitable to vacuum deposition in highfrequency transducers over the conventional quarter-wavelength resonant cavity approach, because thinner layers and more versatile material selection can be used, the difficulty in precisely lapping quarter-wavelength matching layers is avoided, the layers are less attenuating, and the layers can be applied to a curved surface. Two different 3-mm-diameter 45-MHz planar lithium niobate transducers and one geometrically curved 3-mm lithium niobate transducer were designed and fabricated using this matching layer approach with copper as the mass layer and parylene as the spring layer. The first planar lithium niobate transducer used a single mass-spring matching network, and the second planar lithium niobate transducer used a single mass-spring network to approximate the first layer in a dual quarter-wavelength matching layer system in addition to a conventional quarter-wavelength layer as the second matching layer. The curved lithium niobate transducer was press focused and used a similar mass-spring plus quarter-wavelength matching layer network. These transducers were then compared with identical transducers with no matching layers and the performance improvement was quantified. The bandwidth of the lithium niobate transducer with the single mass-spring layer was measured to be 46% and the insertion loss was measured to be -21.9 dB. The bandwidth and insertion loss of the lithium niobate transducer with the mass-spring network plus quarter-wavelength matching were measured to be 59% and -18.2 dB, respectively. These values were compared with the unmatched transducer, which had a bandwidth of 28% and insertion loss of -34.1 dB. The bandwidth and insertion loss of the curved lithium niobate transducer with the mass-spring plus quarter-wavelength matching layer combination were measured to be 68% and -26 dB, respectively; this compared with the measured unmatched bandwidth and insertion loss of 35% and -37 dB. All experimentally measured values were in excellent agreement with theoretical Krimholtz-Leedom-Matthaei (KLM) model predictions